Numerical Simulation of the Thermomechanical Behavior of a Hot Stamping Die - Jiang, Q.Y.; Zhao, H.Y,; Yan, H.F. (Проблемы прочности, 2018)
For studying the temperature field of hot stamping, the effect of the distance between cooling pipes, the distance between the cooling pipe and mold surface, and the water cooling pipe diameter were evaluated with ANSYS software. The results showed that the maximum temperature was about 50°C, and the maximum temperature difference of hot stamping was less than 35°C. The maximum temperature and the uniformity of stamping temperature can be improved by controlling the size and spacing of cooling pipes.